Corporate Governance and Fraud: A Systematic Review - Adelia Ayu Apristiana; Dwi Cahyo Utomo (Politeknik Ganesha Medan, 2025)
The increasing phenomenon of fraud across various business sectors emphasizes the importance of implementing effective corporate governance. Strong corporate governance is believed to enhance company transparency and accountability, thereby reducing the risk of fraud occurrence. This study aims to analyze the role of corporate governance in preventing fraud through a systematic review approach using PRISMA guidelines. It examines 22 articles published between 2020 and 2024 from the Scopus, ScienceDirect, and Emerald Insight databases, focusing on corporate governance and fraud prevention. The findings reveal that the implementation of strong corporate governance mechanisms, such as board independence, gender diversity, board size, audit committees, internal controls, and audit quality, significantly contributes to fraud prevention. However, the effectiveness of these mechanisms depends on cultural, regulatory, and institutional contexts. This study also highlights the importance of Islamic governance in fraud prevention, particularly in the Islamic financial sector, by emphasizing principles of justice, transparency, and the role of the Sharia Supervisory Board (SSB). Overall, effective corporate governance enhances transparency and accountability, reducing the risk of fraud, although further research is needed to explore the variations in the effectiveness of governance mechanisms across different cultural and regulatory contexts.